The relationship between air pollutants and spirometric indices in schoolchildren of five areas in Tehran - Kooranifar, Siavash; Alizadeh Attar, Gholamreza; Talebi, Atefeh; Moradians, Vahan; Pourashraf, Maryam; Rostami, Razieh; Bakhtiari, Nima (Journal of Contemporary Medical Sciences, 2021)
Objectives: The adverse health effects of air pollution have been observed in many epidemiological studies. The aim of this research was to study the effects of air pollution on pulmonary functions in schoolchildren inTehran city. Methods: Atotal number of 167 schoolchildren were selected to participate in this study. Data were analyzed using ANOVA and Generalized Estimating Equation(GEE) to determinethe relationship of air pollution and lung function tests. Results: The result of this study showed that there are statistically significant differences in value of air pollution between areas.The results present that concentration of O3, PM10, NO2 has a negative association with lung function tests but concentration of CO, PM2.5, and SO2 had no association with decreased lung function tests. Time variable of air pollution was not statistically significant effect on lung function test. Conclusion: in this study, we conclude that air pollution in Tehran city can be decreased lung function test indexes that may be affected by short-time exposure to air pollutant.